1002. CISTANCHE DESERTICOLA: Orobanchaceae. (9th November 2021) - Lei, Di; Thorogood, Chris J.; Tu, Pengfei; Song, Yuelin; Huang, Linfang; Aldughayman, Majed; Leon, Christine J.; Hawkins, Julie A.
Summary: Cistanche deserticola Ma is illustrated and described. This species is native to China where it has long been valued and used in Traditional Chinese Medicine and is now cultivated extensively for trade. The species is confused easily with closely related species such as Cistanche salsa (C.A. Mey.) Beck. Bract and vascular bundle morphology, and habit, have been used traditionally to discriminate these taxa, which we discuss. Cistanche deserticola and its relatives may have significant global potential as ancillary crops that could be grown with shelter forests planted to halt land degradation.